'I worked until my body was broken': an ethnomedical model of chronic pain among North Korean refugee women. Issue 5 (4th July 2022) - Park, Soim; Surkan, Pamela J.; Winch, Peter J.; Kim, Jin-Won; Gittelsohn, Joel
ABSTRACT: Objectives: While increasing numbers of North Korean refugees (NKRs) are migrating to South Korea, different understandings of physical pain between NKR patients and the South Korean healthcare providers may create miscommunication and less satisfaction with their care management. To identify strategies to improve care, this study elicits and presents an ethnomedical model of chronic pain among NKR women. Design: Twenty semi-structured individual interviews were conducted with NKR women with chronic pain living in South Korea. Inductive and deductive thematic analysis was performed on three types of data: interview transcripts, field notes created after each interview, and memos written during the analysis. Results: Participants reported that pain started after a certain period of resettlement and expressed frustration when there was no definite diagnosis for pain. They identified physical factors (e.g. excessive labor, exposure to violence, and poor diet) as the primary causes, while psychological factors (e.g. loneliness, rumination, and financial burden of sending remittances to North Korea) were viewed as collateral or contributing causes. Several participants indicated emotional discomfort when they were referred to psychiatrists for unceasing pain. Physical treatment (injections, medications, or acupuncture) and providers' sincere attitudes were expectations of care considered capable of addressing both physical and emotional distress. Conclusions: Findings highlight the need to understand NKR women's ethnomedical model of chronic pain, which is distinct from illness model of healthcare providers. These preliminary findings could be used to improve care strategies based on NKRs' care needs.